2013
DOI: 10.1007/s11205-013-0259-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Macro-Economic Circumstances and Social Protection Expenditure on Economic Deprivation in 25 European Countries, 2007–2011

Abstract: In this study, we investigate to what extent macro-economic circumstances and social protection expenditure affect economic deprivation. We use three items from round five of the European Social Survey (2010-2011) to construct our latent outcome variable, which we label economic deprivation in the 3 years before 2010-2011. The results of our linear multilevel regression analyses indicate that in countries that perform worse economically, individual experiences of economic deprivation are more prevalent: the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…The different magnitudes of absolute inequalities between welfare regimes may be explained by their socioeconomic characteristics, as Former-USSR and Post-Communist countries have traditionally lower social protection expenditure as a percentage of GDP. [ 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…The different magnitudes of absolute inequalities between welfare regimes may be explained by their socioeconomic characteristics, as Former-USSR and Post-Communist countries have traditionally lower social protection expenditure as a percentage of GDP. [ 36 , 37 ]…”
Section: Discussionmentioning
confidence: 99%
“…These three measures have been offered with a seven-point response scale ranging from 0 ('not at all') to 6 ('a great deal'). According to conventional scaling techniques (see Appendix Table 4), these three items form a unidimensional scale that meets statistical tests (Visser et al 2014;Reeskens and van Oorschot 2014). Moreover, Visser et al (2014) have demonstrated the cross-national measurement equivalence of this scale, which makes it suitable for comparative research.…”
Section: Independent Variablementioning
confidence: 99%
“…At the same time, studies hint at a variation in the extent to which economic hardship affects well-being; some people are more resilient in the face of economic hardship than others. To explain this variation, studies have largely focused on the cushioning impact of material or pecuniary resources, and particularly welfare states' ability to buffer the negative consequences of economic hardship (Stuckler et al 2009;Visser et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social expenditure levels seem to depend on unemployment, GDP growth, population ageing, GDP per capita and the openness of an economy (Rozensky, 2014). Visser et al (2014) investigated to what extent macro-economic circumstances and social protection expenditure affect economic deprivation. Their results of linear multilevel regression anal- Renata Halaskova / Montenegrin Journal of Economics, Vol.…”
Section: Literature Reviewmentioning
confidence: 99%